Local Government and its Jurisdiction in Federal Nepal: A Theoretical Analysis - Gurung, Yam Kumari (Journal of Development Review, 2024)
This paper examines jurisdiction power of local government in federal Nepal. Specifically, it entails on how the local bodies exercised their jurisdictional power on the system of federal. Local government administration in federal Nepal are now struggling the high degree of autonomy. Even, 80 percent of the Local laws are delegated or the secondary law. Presently, 70.16 percent male and 17.93 percent female elected representatives headed the LGs. Most of the employees are disinterested to join the local bodies. Further, Local bodies are highly ineffective and inefficient due to concentration of power at the center, inadequate fund, grants, loans and limited resources. The study is based on secondary data with descriptive design of qualitative method. Therefore, local bodies of federal Nepal has equal share of power, equitable distribution of fiscal transfer and the all-inclusive participation.